Unearthing Gender : Folksongs of North India - Jassal, Smita Tewari (Book collections on Project MUSE., 2012)
This book is a compelling ethnographic analysis of folksongs sung primarily by lower-caste women in north India, in the fields, at weddings, during travels, and in other settings. Smita Tewari Jassal uses these songs to explore how ideas of caste, gender, sexuality, labor, and power may be strengthened, questioned, and fine-tuned through music. At the heart of the book is a library of songs, in their original Bhojpuri and in English translation, framed by Jassal's insights into the complexities of gender and power. The significance of these folksongs, Jassal argues, lies in their suggesting and hinting at themes, rather than directly addressing them: women sing what they often cannot talk about. Women's lives, their feelings, their relationships, and their social and familial bonds are persuasively presented in song. For the ethnographer, the songs offer an entry into the everyday cultures of marginalized groups of women who have rarely been the focus of systematic analytical inquiry.